AB0209 Gli-Inhibitors Simultaneously Target Canonical and Non-Canonical Hedgehog Pathways and Ameliorate the Pro-Fibrotic Effects of Transforming Growth Factor-β. (9th June 2015) - Liang, R.; Dess, C.; Palumbo-Zerr, K.; Lin, N.-Y.; Zhang, Y.; Distler, O.; Schett, G.; Distler, J.
Abstract : Background: Hedgehog signalling plays a key-role in the pathogenesis of fibrosis in SSc. Besides the canonical hedgehog pathway with activation of Gli transcription factors via ligand-binding to the cell surface receptors, Gli can be activated independently of classical hedgehog ligands and receptors (so-called non-canonical pathways). Objectives: The aim of the present study was to evaluate the role of non-canonical hedgehog signalling in SSc and to test the efficacy of direct Gli-inhibitors that target simultaneously canonical and non-canonical hedgehog pathways. Methods: The Gli-inhibitor GANT-61 was used to inhibit canonical as well as non-canonical hedgehog signalling, while the smo-inhibitor vismodegib was used to selectively target canonical hedgehog signalling. The effects of inhibition of Gli2 on TGF-β signalling were analysed in cultured fibroblasts, in the mouse model of bleomycin-induced pulmonary fibrosis and in a model of fibrosis induced by overexpression of a constitutively active TGF-b receptor I (TBRI) in vivo. Results: TGF-β upregulated the expression of Gli2 in cultured fibroblasts and in murine skin by direct transcriptional regulation. TGF-β as well as its downstream mediator phosphorylated Smad3 were co-expressed with Gli-2 in the skin of SSc patients. Consistent a novel role of Gli2 as a downstream mediator of TGF-β in fibroblasts, inhibition of Gli2 by GANT-61 ameliorated the stimulatory effects of TGF-β on fibroblasts in vitro and in vivo. Treatment with GANT-61 downregulated the mRNA levels of prototypical TGF-b targeted genes, whereas inhibition of canonical hedgehog signalling had no effects. Moreover, GANT-61 reduced the mRNA levels of col1a2 and the release of collagen protein. GANT-61 also blocked TGF-b-induced myofibroblast differentiation and decreased the levels of a-smooth muscle actin and the formation of stress fibres. Moreover, GANT-61 ameliorated experimental fibrosis of the skin and lungs more efficiently as compared to vismodegib. In the model of TBRI-induced fibrosis, mice treated with GANT-61 showed reduced dermal thickening, lower myofibroblast counts and decreased the hydroxyproline content. In contrast, vismodegib had no anti-fibrotic effect in this model. GANT-61 also exerted potent anti-fibrotic effects in the model of bleomycin-induced pulmonary fibrosis and induced regression of pre-established fibrosis. In both models, GANT-61 did not only reduce levels of the hedgehog target genes, but also the levels of the TGF-b target genes PAI-1, CTGF and Smad7, thus confirming inhibition of TGF-b signalling upon targeting of Gli2. Conclusions: We characterize Gli2 as a novel intracellular mediator of the pro-fibrotic effects of TGF-b. Pharmacologic inhibition of Gli2 targets canonical as well as non-canonical hedgehog signalling and ameliorates the pro-fibrotic effects of TGF-b. The potent anti-fibrotic effects of Gli2 inhibitors on cultured fibroblasts, dermal and pulmonary fibrosis and availability of Gli2 inhibitors for clinical use encourage additional studies to further explore the potential of Gli2 inhibitors for the treatment of fibrosis. Disclosure of Interest: R. Liang Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, C. Dess Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, K. Palumbo-Zerr Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, N.-Y. Lin Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, Y. Zhang Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, O. Distler Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, G. Schett Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no, J. Distler Shareholder of: no, Grant/research support from: no, Consultant for: no, Employee of: no, Paid instructor for: no, Speakers bureau: no